Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/jrr/rry068
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate radiation dose for symptomatic relief and local control in patients with adult T cell leukemia/lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATL) is an aggressive peripheral T-cell neoplasm that occurs only in patients with human T-cell leukemia virus type 1. No large study or randomized trial investigating radiotherapy (RT) for ATL has been performed. We retrospectively reviewed 55 courses of RT for 41 consecutive patients with ATL who underwent RT between 2000 and 2016 at our institutions. The results showed that RT for local ATL lesions can achieve symptomatic improvement in 92% of cases. Local remission, either c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They suggested detecting clonal T cell receptor-g gene rearrangements is useful for the evaluation of therapeutic effects and the early detection of lymphoma recurrence. Maemoto et al 27 retrospectively reviewed 55 courses of radiotherapy for 41 ATLL patients, showed that symptomatic improvement was achieved in 92% of cases, and the mean total radiation dose in the complete and partial response groups differed significantly, was 38 and 25 Gy, respectively. Recently, Xu et al 28 found that hypericin was highly effective against ATLL cells by induction of apoptosis and suppression of viral transcription, highlighted the promising use of hypericin-photodynamic therapy as a targeted therapy for ATLL.…”
Section: Skin-targeted Therapymentioning
confidence: 99%
“…They suggested detecting clonal T cell receptor-g gene rearrangements is useful for the evaluation of therapeutic effects and the early detection of lymphoma recurrence. Maemoto et al 27 retrospectively reviewed 55 courses of radiotherapy for 41 ATLL patients, showed that symptomatic improvement was achieved in 92% of cases, and the mean total radiation dose in the complete and partial response groups differed significantly, was 38 and 25 Gy, respectively. Recently, Xu et al 28 found that hypericin was highly effective against ATLL cells by induction of apoptosis and suppression of viral transcription, highlighted the promising use of hypericin-photodynamic therapy as a targeted therapy for ATLL.…”
Section: Skin-targeted Therapymentioning
confidence: 99%